2023
DOI: 10.1038/s41746-023-00908-6
|View full text |Cite
|
Sign up to set email alerts
|

Implications for implementation and adoption of telehealth in developing countries: a systematic review of China’s practices and experiences

Jiancheng Ye,
Lu He,
Molly Beestrum

Abstract: The rapid advancement of telehealth technologies has the potential to revolutionize healthcare delivery, especially in developing countries and resource-limited settings. Telehealth played a vital role during the COVID-19 pandemic, supporting numerous healthcare services. We conducted a systematic review to gain insights into the characteristics, barriers, and successful experiences in implementing telehealth during the COVID-19 pandemic in China, a representative of the developing countries. We also provide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 87 publications
3
10
0
Order By: Relevance
“…For instance, studies from China [ 11 ], Saudi Arabia [ 10 ], and India [ 12 ] show varying levels of telemedicine readiness and receptivity, owing to disparities in healthcare systems and digital infrastructure. Similar studies have been conducted with healthcare professionals and students in a variety of countries, such as Saudi Arabia [ 13 ], Indonesia [ 14 ], Pakistan [ 15 ], and the United Arab Emirates [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, studies from China [ 11 ], Saudi Arabia [ 10 ], and India [ 12 ] show varying levels of telemedicine readiness and receptivity, owing to disparities in healthcare systems and digital infrastructure. Similar studies have been conducted with healthcare professionals and students in a variety of countries, such as Saudi Arabia [ 13 ], Indonesia [ 14 ], Pakistan [ 15 ], and the United Arab Emirates [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These disparities highlight the impact of diverse healthcare infrastructures, the accessibility of digital technologies, and the existence or nonexistence of training programs linked to telemedicine in diverse contexts. These variations highlight the need for region-specific telemedicine strategies that take into account the particular requirements and environments of each area [9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health policymakers and administrators must consider the integration of telehealth into existing healthcare frameworks, addressing regulatory, reimbursement, and infrastructure challenges [ 14 ]. The success of telemedicine in reducing non-emergent ER visits depends on a multifaceted approach that involves not only individual adoption but also systemic support and integration [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 32 , 33 Evidence also indicated that some healthcare providers with specific specialties, such as primary care and psychiatry, have a higher knowledge and awareness of TM due to its direct relevance to their practice. 4 , 20 , 34 , 35 years of experience within the healthcare specialty is another factor that increases TM awareness among healthcare providers. 4 , 34 , 36 , 37 The healthcare providers’ geographical locations have a positive association with the level of TM awareness due to their potential to address healthcare disparities and improve access to care in remote regions.…”
Section: Introductionmentioning
confidence: 99%